State and Trends of Carbon Pricing 2022 - World Bank (Washington, DC: World Bank, 2022)
This report provides an up-to-date overview of existing and emerging carbon pricing instruments around the world, including international, national and subnational initiatives. It also investigates trends surrounding the development and implementation of carbon pricing instruments and how they could accelerate the delivery of long-term mitigation goals. Specifically, this includes the use of carbon taxes, emissions trading systems and crediting mechanisms. Key topics covered in the 2022 report include cross-border approaches to carbon pricing, challenges and opportunities from rising energy prices, and new technologies and governance frameworks shaping carbon markets.